Long-term climatological trends driving the recent warming along the Angolan and Namibian coasts - Folly Serge Tomety; Serena Illig; Marek Ostrowski; Founi Mesmin Awo; Marie-Lou Bachèlery; Noel Keenlyside; Mathieu Rouault (Climate Dynamics, 2024)
The coastal regions off Angola and Namibia are renowned for their highly productive marine ecosystems in the southeast Atlantic. In recent decades, these regions have undergone significant long-term changes. In this study, we investigate the variability of these long-term changes throughout the annual cycle and explore the underlying mechanisms using a 34-year (1982–2015) regional ocean model simulation. The results reveal a clear seasonal dependence of sea surface temperature (SST) trends along the Angolan and Namibian coasts, with alternating positive and negative trends. The long-term warming trend in the Angolan coastal region is mainly explained by a pronounced warming trend in the austral spring and summer (November-January), while the decadal trend off Namibia results from a counterbalance of an austral winter cooling trend and an austral summer warming trend. A heat budget analysis of the mixed-layer temperature variations shows that these changes are explained by a long-term modulation of the coastal currents. The Angolan warming trend is mainly explained by an intensification of the poleward coastal current, which transports more warm equatorial waters towards the Angolan coast. Off Namibia, the warming trend is attributed to a reduction in the northwestward Benguela Current, which advects cooler water from the south to the Namibian coast. These changes in the coastal current are associated with a modulation of the seasonal coastal trapped waves that are remotely-forced along the equatorial waveguide. These long-term changes may have significant implications for local ecosystems and fisheries.

Intraseasonal descriptors and extremes in South African rainfall. Part II : Summer teleconnections across multiple timescales - Asmat Ullah; Benjamin Pohl; Julien Pergaud; Bastien Dieppois; Mathieu Rouault (International Journal of Climatology, 2023)
Extreme events contribute significantly to rainfall variability in semi‐arid regions like South Africa. Here, following the definition of a novel typology of rainfall extremes, disentangling large‐ and small‐scale events in Part I, we use quality‐controlled observational databases in South Africa, the ERA5 reanalysis and satellite estimates TRMM‐3B42 to examine the relationship between these two types of rainfall extremes and different modes of climate variability at various timescales. At low frequencies, rainfall extremes are assessed at interannual (IV: 2–8 years) and quasi‐decadal (QDV: 8–13 years) timescales, which are primarily associated with the El Niño–Southern Oscillation (ENSO) and the Interdecadal Pacific Oscillation (IPO), respectively. At subseasonal timescales, the typology of rainfall extremes is analysed depending on the synoptic configurations, as inferred by seven convective regimes including tropical temperate troughs (TTTs: 3–7 days), and the intraseasonal variability associated with the Madden–Julien Oscillation (MJO: 30–60 days). At the IV timescale, the occurrence of large‐scale extremes is substantially higher during its wet phases thereby suggesting a 400% rise in the occurrence of large‐scale extremes as compared to its dry phases. At the QDV timescale, variability mostly relates to the modulation of small‐scale extremes during its wet phases. Teleconnections with global sea surface temperature (SST) confirm that La Niña conditions favour overall wet conditions and extremes in South Africa. The numbers of large‐scale extremes are consistently related to warmer SSTs in the North Atlantic, while their link with warmer Indian and tropical South Atlantic oceans is found to be statistically independent of the state of ENSO. At the subseasonal timescales, large‐scale extremes largely occur during three out of the seven convective regimes identified in the southern African region whereas small‐scale extremes are nearly equiprobable during all convective regimes. The occurrence of large‐scale extremes during continent‐rooted TTT is further enhanced during the locally wet phases of the MJO and is symmetrically weakened during its dry phases.

Physical processes and biological productivity in the upwelling regions of the tropical Atlantic - Peter Brandt; Gaël Alory; Founi Mesmin Awo; Marcus Dengler; Sandrine Djakouré; Rodrigue Anicet Imbol Koungue; Julien Jouanno; Mareike Körner; Marisa Roch; Mathieu Rouault (Ocean Science, 2023)
In this paper, we review observational and modelling results on the upwelling in the tropical Atlantic between 10∘ N and 20∘ S. We focus on the physical processes that drive the seasonal variability of surface cooling and the upward nutrient flux required to explain the seasonality of biological productivity. We separately consider the equatorial upwelling system, the coastal upwelling system of the Gulf of Guinea and the tropical Angolan upwelling system. All three tropical Atlantic upwelling systems have in common a strong seasonal cycle, with peak biological productivity during boreal summer. However, the physical processes driving the upwelling vary between the three systems. For the equatorial regime, we discuss the wind forcing of upwelling velocity and turbulent mixing, as well as the underlying dynamics responsible for thermocline movements and current structure. The coastal upwelling system in the Gulf of Guinea is located along its northern boundary and is driven by both local and remote forcing. Particular emphasis is placed on the Guinea Current, its separation from the coast and the shape of the coastline. For the tropical Angolan upwelling, we show that this system is not driven by local winds but instead results from the combined effect of coastally trapped waves, surface heat and freshwater fluxes, and turbulent mixing. Finally, we review recent changes in the upwelling systems associated with climate variability and global warming and address possible responses of upwelling systems in future scenarios.

Intraseasonal descriptors and extremes in South African rainfall. Part I: Summer climatology and statistical characteristics - Asmat Ullah; Benjamin Pohl; Julien Pergaud; Bastien Dieppois; Mathieu Rouault (International Journal of Climatology, 2022)
Rainfall extremes are of major and increasing importance in semi‐arid countries and their variability has strong implications for water resource and climate impacts on the local societies and environment. Here, we examine intraseasonal descriptors (ISDs) and wet extremes in austral summer rainfall (November–February) over South Africa (SA). Using daily observations from 225 rain gauges and ERA5 reanalysis between 1979 and 2015, we propose a novel typology of wet extreme events based on their spatial fraction, thus differentiating large‐ and small‐scale extremes. Long‐term variability of both types of extreme rainfall events is then extensively discussed in the context of ISDs. The results demonstrate that using 7% of spatial fraction simultaneously exceeding the local threshold of the 90th percentile produces remarkable results in characterizing rainfall extremes into large‐ and small‐scale extremes. Austral summer total rainfall is found to be primarily shaped by large‐scale extremes which constitute more than half of the rainfall amount under observation, and nearly half in ERA5. Observation (ERA5) shows an average of 8 ± 5 (20 ± 7) days per season associated with large‐scale extremes, which are comprised in 5 ± 3 (10 ± 3) spells with an average persistence of at least 2 days. Overall, we find a strong dependence of total rainfall on the number of wet days and wet spells that are associated with large‐scale extremes. We also find that large‐ and small‐scale extremes are well‐organized and spatially coherent in nature yet extreme conditions during small‐scale events are found sporadic over the region, contrasting with large‐scale events for which extreme conditions are found over a larger and coherent region.

Southern African summer-rainfall variability, and its teleconnections, on interannual to interdecadal timescales in CMIP5 models - Bastien Dieppois; Benjamin Pohl; Julien Crétat; Jonathan Eden; Moussa Sidibe; Mark New; Mathieu Rouault; Damian Lawler (Climate Dynamics, 2019)

The impact of ENSO on Southern African rainfall in CMIP5 ocean atmosphere coupled climate models - Bastien Dieppois; Mathieu Rouault; Mark New (Climate Dynamics, 2015)

Spatial dynamics of the bearded goby and its key fish predators off N amibia vary with climate and oxygen availability - Anne Gro V. Salvanes; Chris Bartholomae; Dawit Yemane; Mark J. Gibbons; Paul Kainge; Jens‐Otto Krakstad; Mathieu Rouault; Arved Staby; Svein Sundby (Fisheries Oceanography, 2015)
Hypoxia [O 2 −1 (87 μ mol kg −1 )] and severely hypoxic water masses [O 2 −1 (21.8 μ mol kg −1 )] are increasing in coastal marine ecosystems due to eutrophication and warming. Here, we investigate the response of the suboxic‐tolerant endemic fish, Sufflogobius bibarbatus , to variations in the thermal and oxygen environment, as well as to predation pressure, using 22 yr worth of satellite and in situ data. We show that environmental variation and predation pressure affect the goby population, which has expanded over the last decade while that of horse mackerel has contracted. These changes co‐occurred with a general warming in the north and central shelf areas (north of 24.5°S). Spring warming positively affected both goby and hake abundances, but not the horse mackerel, suggesting different responses to surface temperature. The goby habitat contracted when predators were abundant, particularly in the north, which is the fringe of its distributional area. The implications of the differential tolerance of gobies and their predators for climate variations are discussed.

Simulation of the annual and diurnal cycles of rainfall over South Africa by a regional climate model - Benjamin Pohl; Mathieu Rouault; Shouraseni Sen Roy (Climate Dynamics, 2014)

The diurnal cycle of rainfall in South Africa in the austral summer - Mathieu Rouault; Shouraseni Sen Roy; Robert C. Balling (International Journal of Climatology, 2013)
The diurnal cycle of precipitation over South Africa during summer is analysed for the first time using hourly precipitation data from 103 stations for the period 1998–2007. Using harmonic analysis, we found the presence of a distinct diurnal cycle over most of South Africa regarding both the frequency and amount of precipitation events. The standardized amplitudes, indicative of the strength of the diurnal cycle across a region, are strongest over the interior and along the east coast of South Africa with up to 70% explained variance associated with the diurnal cycle. The time of maximum precipitation is late afternoon to early evening in the interior, and midnight to early morning along the Agulhas Current as well as inland in the northeast of the county. The proximity of the warm Agulhas Current plays a role in the diurnal cycle of rainfall at coastal stations. There is an early morning maximum in precipitation in the South West of the country with small amplitude in the diurnal cycle there. On average, the peak in precipitation amount leads the peak in frequencies of precipitation by 30 min to 1 h. Together with a high resolution climatological summer rain rate presented here and a detailed table for all stations, this study is a benchmark upon which model output or satellite estimate of the diurnal cycle can be compared within the region. Copyright © 2012 Royal Meteorological Society

Multi-month memory effects on early summer vegetative activity in semi-arid South Africa and their spatial heterogeneity - Yves Richard; Nadège Martiny; Mathieu Rouault; Nathalie Philippon; Yann Tracol; Thierry Castel (International Journal of Remote Sensing, 2012)

Recurrent daily rainfall patterns over South Africa and associated dynamics during the core of the austral summer - Julien Crétat; Yves Richard; Benjamin Pohl; Mathieu Rouault; Chris Reason; Nicolas Fauchereau (International Journal of Climatology, 2012)
This paper investigates the influence of some modes of climate variability on the spatio‐temporal rainfall variability over South Africa during the core of the rainy season, December to February (DJF). All analyses are based directly on the rainfall field instead of atmospheric processes and dynamics. An original agglomerative hierarchical clustering approach is used to classify daily rainfall patterns recorded at 5352 stations from DJF 1971 to DJF 1999. Five clusters are retained for analysis. Amongst them, one cluster looks most like the rainfall and circulation mean picture. Another one, representing 37% of the days, describes strong negative rainfall anomalies over South Africa resulting from a regional barotropic trough‐ridge‐trough wave structure and moisture divergence. These dry anomalies are more frequent in El Niño years (with a 0.75 correlation between ENSO and the seasonal occurrences of that cluster) and are associated with a weakening and/or a regional shift of the Walker‐type circulation and the subtropical jet stream. Three clusters, which describe, respectively, a decrease, an increase, and a conservation of the seasonal mean eastward rainfall gradient, are all associated with strong cyclonic moisture flux anomalies centred over Angola or northern Botswana and the anomalous convergence located over the largest positive rainfall anomalies, suggesting the importance of thermal low pressures. One of them is clearly associated with tropical temperate troughs. The rainfall patterns of these three clusters tend to propagate eastward, and their seasonal frequencies tend to increase in La Niña years. Copyright © 2010 Royal Meteorological Society

20th century droughts in southern Africa: spatial and temporal variability, teleconnections with oceanic and atmospheric conditions - Yves Richard; Nicolas Fauchereau; Isabelle Poccard; Mathieu Rouault; Sylwia Trzaska (International Journal of Climatology, 2001)
Southern African rainfall does not show any trend to desiccation during the 20th century. However, the subcontinent experienced particularly severe droughts in the 1980s and at the beginning of the 1990s and the magnitude of the interannual summer rainfall variability shows significant changes. Modifications of the intensity and spatial extension of droughts is associated with changes in ocean–atmosphere teleconnection patterns. This paper focuses mostly on the well‐documented 1950–1988 period and on late summer season (January–March). A principal component analysis on southern African rainfall highlights modifications of the rainfall variability magnitude. The 1970–1988 period had more variable rainfall, and more widespread and intense droughts than the 1950–1969 period. To investigate the potential modifications of the associated ocean–atmosphere teleconnection patterns, a composite analysis is performed on sea‐surface temperature (SST) and National Center for Environmental Protection (NCEP) atmospheric parameters, according to the 5 driest years of both sub‐periods. Significant changes are shown in ocean–atmosphere anomaly patterns coincident with droughts for both sub‐periods. The 1950–1969 droughts were associated with regional ocean–atmosphere anomalies, mainly over the southwest Indian Ocean region. In contrast, during the 1970–1988 droughts near‐global anomalies were observed in the tropical zone, corresponding to El Niño–Southern Oscillation (ENSO) phenomenon. Within the whole century, significant correlations between Southern Oscillation Index (SOI) and southern African Rainfall Index (SARI) were found in the periods (1900–1933 and 1970–1998) when SOI and SARI experienced high variability, and when southern Africa was affected by intense and extended droughts. During periods of low SOI (1934–1969), correlations became less significant and droughts were less intense and widespread. Copyright © 2001 Royal Meteorological Society

ATMOSPHERIC BOUNDARY-LAYER FLUXES AND STRUCTURE ACROSS A LAND-SEA TRANSITION ZONE IN SOUTH-EASTERN AFRICA - MARK JURY; MATHIEU ROUAULT; SCARLA WEEKS; MARK SCHORMANN (Boundary-Layer Meteorology, 1997)